Mathematical insights into neuroendocrine transdifferentiation of human prostate cancer cells: Mathematical insights into neuroendocrine transdifferentiation of human prostate cancer cells - Turner, Leo; Burbanks, Andrew; Cerasuolo, Marianna (Nonlinear Analysis: Modelling and Control, 2021)
Prostate cancer represents the second most common cancer diagnosed in men and the fifth most common cause of death from cancer worldwide. In this paper, we consider a nonlinear mathematical model exploring the role of neuroendocrine transdifferentiation in human prostate cancer cell dynamics. Sufficient conditions are given for both the biological relevance of the model’s solutions and for the existence of its equilibria. By means of a suitable Liapunov functional the global asymptotic stability of the tumour-free equilibrium is proven, and through the use of sensitivity and bifurcation analyses we identify the parameters responsible for the occurrence of Hopf and saddle-node bifurcations. Numerical simulations are provided highlighting the behaviour discovered, and the results are discussed together with possible improvements to the model.
Keywords: prostate cancer; neuroendocrine transdifferentiation; mathematical model; sensitivity analysis; bifurcation